Ontogenetic Development of Hedysarum alpinum L. in the Prebaikalia Region (Global Journal of Science Frontier Research, 2020)
Hedysarum alpinum L. is an important medicinal plant, which also has ornamental value and is used as a non-conventional feed resource. The medicinal value of this plant species is attributable to the content of the glycoside mangiferin in the aerial parts of a plant, which demonstrates immunostimulating properties. Harvesting of H. alpinum as a herbal raw material leads to a fast depletion of natural coenopopulation areas. When cultivated in Prebaikalia, the plant passes through all ontogenetic stages, entering the reproductive phase at year 2-3 of growth. The mid-reproductive stage, which is the most productive for feeding purposes, lasts 6 to 10 years. For introduced species, the life span of a plant growing in the same place ranges between 12 and 20 years. H. alpinum is a promising medicinal and fodder plant, which tolerates dry summer periods, is winter-hardy, and has high shoot biomass production.
Keywords: hedysarum alpinum; fodder plant; medicinal; ornamental; ontogenesis; introduction